Aircraft design studies - counter insurgency aircraft with suction boundary layer control - Howe, D. (Cranfield Institute of Technology; College of Aeronautics, 1970)
A design study of a counter insurgency aircraft with a suction boundary layer controlled wing to give high lift has been undertaken. The work was carried out by the students in the Department of Aircraft Design during the 1966 academic year and was intended to provide evidence on the feasibility of the configuration employed. The aircraft has a gross weight of 9800 lb. and is designed to carry a variety of payloads of up to 2000 lb. at a maximum speed of 380 m. p. h. The flight usable lift coefficient of five is achieved at an incidence of approximately 30 o which introduced particular layout and undercarriage problems. A twin boom configuration with a variable geometry undercarriage was adopted. It is concluded that the use of a suction boundary layer control system can confer significant performance benefits but the aircraft might well be handicapped by climatic operational limitations. The variable geometry undercarriage is complex and an alternative layout using a tilt wing might be preferable.